ChemInform Abstract: Nanocrystalline Fe83P16Cu1 Soft Magnetic Alloy Produced by Crystallization of Its Amorphous Precursor. Issue 9 (5th March 2013) - Chen, F. G.; Wang, Y. G.; Miao, X. F.; Hong, H.; Bi, K.
Abstract The title alloy is prepared by melt‐spinning from mixtures of Fe, P—Fe alloy, and Cu in a high‐purity argon atmosphere followed by annealing at 563 K for 2 min.